Tonggyu-tang, a traditional Korean medicine, suppresses pro-inflammatory cytokine production through inhibition of MAPK and NF-κB activation in human mast cells and keratinocytes - Hyo In Kim; Se Hyang Hong; Jin Mo Ku; Sooyeon Kang; Tai Young Kim; Yong Cheol Shin; Seong-Gyu Ko (BMC, 2017)
Abstract Background Allergic diseases including allergic rhinitis, asthma, and atopic dermatitis are increasing worldwide. Common medications used to treat these inflammatory disorders are anti-histamines and corticosteroids, but they have their own limitations such as short duration and severe side effects. Thus, interest in complementary and alternative medicine is continually growing. Here, we investigate the anti-inflammatory mechanisms of Tonggyu-tang (TGT), a traditional Korean medicine that has been used to treat patients with allergic nasal disorders. Methods We measured mRNA expressions and production of pro-inflammatory cytokines such as interleukin (IL)-4, IL-6, IL-8 and tumor necrosis factor alpha (TNF-α) by RT-PCR and ELISA assays in HMC-1 (human mast cell line-1) and HaCaT cells, immortalized human keratinocytes. Moreover, we evaluated the effect of TGT on two major inflammation-related pathways, mitogen activated protein kinase (MAPK) and NF-κB signaling pathway in these two cells. Results Our results revealed that that TGT significantly reduced the expression and production of inflammatory cytokines such as IL-4, IL-6, IL-8, and TNF-α in the agonist-treated HMC-1 and HaCaT cells. We also found that TGT suppressed MAPK signaling pathway including extracellular signal-regulated kinase (ERK), p38 mitogen-activated protein kinase (p38), and c-Jun N-terminal kinase (JNK) as well as NF-κB pathway, which are known to regulate inflammatory cytokine expression. Conclusion Taken together, our results demonstrate that TGT inhibits expression of pro-inflammatory cytokines by suppressing MAPK and NF-kB pathway in both mast cells and keratinocytes, suggesting the potential use of TGT in treating allergic inflammatory diseases.